Institutions of collective action and smallholder performance: Evidence from Senegal - Wouterse, Fleur; Faye, Amy (International Food Policy Research Institute, 2020)
In this chapter, we use recent data on almost 7,000 smallholders and 395 water user associations (WUAs), along with propensity score matching (PSM) and regression analysis, to quantitatively assess whether membership in producer organizations affects technical efficiency of smallholders and whether the design and governance of such organizations affects the organizations’ performance. Our results reveal that membership is associated with greater efficiency and that the design of organizations and their governance can enhance their commercial performance. Policymakers would thus do well to work with producer organizations and further build their governance capacity and membership base for successful implementation of the country’s agricultural development strategy.